KEBIJAKAN PENYELENGGARAAN REFORMASI BIROKRASI PADA PEMERINTAH KABUPATEN BEKASI - Aos Kuswandi; Siti Nuraini; Rina Susanti Hartono (Governance, 2023)
In the development of the Indonesian government, bureaucratic reform has lagged behind reforms in the political, economic, and legal fields. The first wave of government bureaucratic reform was gradually implemented in 2004 and the second phase in 2010. In 2025, Indonesia is expected to be in a phase that is truly moving towards a developed country and the strength of a professional and high-integrity government bureaucracy. Efforts to achieve the goals of bureaucratic reform are carried out through the stipulation of Presidential Regulation no. 81 of 2010 concerning the Grand Design of Bureaucratic Reform 2010-2025, it is very necessary to be supported by the provincial and district/city governments. This study describes the results of research on the implementation of bureaucratic reform in the Bekasi Regency Government. The results of the study indicate that it is important for the Bekasi Regency Government to formulate and establish the Grand Design for Bureaucratic Reform as the master plan that contains the policy direction for implementing bureaucratic reform within the Bekasi district government. As an operational medium in the medium term, the Bureaucratic Reform Road Map needs to be drawn up and carried out every 5 (five) years and is a detailed plan for bureaucratic reform from one stage to the next for five years with clear annual targets. Bureaucratic reform in Bekasi Regency needs to revise and develop various regulations, modernize various government management policies and practices, and adapt the tasks of regional work unit functions to new paradigms and roles.